African Social Values and the Contemporary Issues of Respect and Cooperation in Nigeria's Educational Process (2020)
The interdependence of social values and education is mutual because one promotes the other. Whoever passes through the process of education is expected to acquire social values which will differentiate him/her from those without the opportunity. Thus, better social behaviour is expected from educated individuals, although there may be exceptions. In other words, the knowledge acquired from schools should expose recipients lo live rightly and harmoniously with others around them. This philosophical piece therefore examines African social values in relation to respect and cooperation as well as its place in the contemporary African society. The need for Teacher Education practitioners especially, in Nigeria to lay more emphasis on the affective domain of learning as recommended in the paper suggests a possible turn-out of learners from schools with better altitudes and display of characters necessary for desired growth and development of the society.